1992
DOI: 10.1159/000282379
|View full text |Cite
|
Sign up to set email alerts
|

Bellini Duct Carcinoma of the Kidney

Abstract: We report a very rare case of Bellini duct carcinoma originating from the collecting tubules of the kidney. A left renal tumor was detected during a health examination and radical nephrectomy was performed. Histological examination showed papillary adenocarcinoma. By means of immunohistochemical methods, we felt that the tumor was a renal carcinoma of Bellini duct origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In diagnosis of CDC, it is important to distinguish between invasive papillary RCC and urothelial carcinoma. Positive immunohistochemical staining for distal tubules and collecting duct markers is helpful indiscrimination of CDC from the more commonly diagnosed clear cell RCC of proximal nephron origin [5]. CDC generally expresses broad spectrum keratins and high molecular weight (HMW) cytokeratin, which is expressed in the lower nephron and the urothelium.…”
Section: Introductionmentioning
confidence: 99%
“…In diagnosis of CDC, it is important to distinguish between invasive papillary RCC and urothelial carcinoma. Positive immunohistochemical staining for distal tubules and collecting duct markers is helpful indiscrimination of CDC from the more commonly diagnosed clear cell RCC of proximal nephron origin [5]. CDC generally expresses broad spectrum keratins and high molecular weight (HMW) cytokeratin, which is expressed in the lower nephron and the urothelium.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor's positivity for high-molecular-weight keratins supports an origin from the distal nephron [7,10,22]. Thus, immunohistochemistry can provide further evidence of its originating from the collecting ducts and is helpful to establish the diagnosis.…”
Section: Discussionmentioning
confidence: 84%
“…Also prior immunohistochemical studies of usual RCC have shown expression of LMWCK, CK19, EMA, VIM, Leu-M1, lysozyme and sometimes PNA but not HMWCK and UEA-1 [8,9,22]. Positivity of HMWCK supports the diagnosis of the CDC since these antigens are normally expressed in the distal tubules and collecting ducts but not in the proximal tubular epithelium [7,10,22]. This immunohistochemical profile changes especially for sarcomatoid variants such as negativity or less positivity of HMWCK according to the nonsarcomatoid CDC [1,22].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…C D C frequently presents as a renal mass causing flank pain and hematuria (Dimopoulos et al, 1993). These lesions are often mistaken preoperatively for RCC or transitional cell carcinoma (TCC) of the renal pelvis and CDC frequently shows evidence of metastatic disease (Mancilla-Jimenez et al, 1976;Cromie et al, 1979;Aizawa et al, 1986;Fleming and Lewi, 1986;Kennedy et al, 1990;Rumpelt et al, 1991;Carter et al, 1992;Fuzesi et al, 1992;Miyamoto et al, 1992;Dimopoulos et al, 1993;Halenda et al, 1993). CDCs can be differentiated from RCC on the basis of a constellation of gross and microscopic features (Table 1).…”
mentioning
confidence: 99%